Characterization of Wall Painting Fragments from the West Courtyard Passage at St. Nicholas Church in Demre - Oğuz Emre Kayser; Özden Ormancı; Ali Akın Akyol (Art-Sanat)
This paper presents archaeometric analyses of representative wall painting fragments (dated to middle Byzantine period) from the West Courtyard Passage at Demre St. Nicholas Church (in ancient Myra), which is located in Antalya province today. Wall painting fragments were analyzed by a multi analytical methods which includes physical and chromametric determinations, optical microscopy, X-ray diffraction (XRD), Raman spectrometry and X-ray fluorescence spectrometry (μ-XRF and PED-XRF), in order to identify the characteristics of the materials, painting technique and the pigments used. Microscopic examinations showed that the samples were two-layered (intonaco and arriccio) wall paintings that executed using the secco technique. The elemental compositions of the plasters are quite similar. The pigments used in the wall paintings is similar to others in the literature, including red and yellow ochre, calcite, green earth (celadonite) and carbon black. Archaeometric studies for the identification of archaeological pigments are carried out with micro-Raman spectroscopy and multiple analytical techniques. The same methodology was applied in this study. The results obtained will also contribute to the conservation/restoration studies of wall paintings.